Baculovírus: produção in vitro do bioinseticida anticarsia e construção de vetor de expressão para glicoproteína (GPV) do rabies lyssavirus - Andrade, Adrielly Silva Albuquerque de (2019)
Baculoviruses are excellents agents for controlling the insect population in the wild and therefore have been successfully used as viral bioinsecticides in agriculture. Moreover, thanks to the knowledge of the in vitro infection process in host cells, baculoviruses are also used as recombinant protein expression vectors. Thus, the present study aimed to produce in vitro wild and recombinant baculovirus in insect cells for future application as viral bioinsecticide and expression of recombinant proteins. For this, the IPLB-SF21 insect cells, adapted to the suspension culture, were used in the first (P1), second (P2) and third pass (P3) Anticarsia gemmatalis multiple nucleopolyhedrovirus (AgMNPV) extracellular virus infection processes. The variables analyzed were cell growth and viability, substrate consumption and viral productivity of the different passages of the viral inoculum in the infection processes. The data obtained were used to determine the kinetic parameters: Specific growth rate (μx); Substrate consumption (qS) and; Production of occlusion bodies (qOB). As a result, the control cells had a μx equal to 0,570 d-1 and the infected cells presented infection rates 0,204 d-1 (P1), 0,131 d-1 (P2) and 0,335 d-1 (P3), indicating that baculovirus reduced the growth of infected cells when compared to control cells. As for qOB, 0,93 OB(mL.d-1), 0,70 OB(mL.d-1) and 1,34 OB(mL.d- 1) were obtained for P1, P2 and P3, respectively, and it can be seen that it is directly proportional to the concentration of infected viable cells. Based on these velocities, it was possible to calculate the yield of polyhedra per milligram of glucose, 1,18x106 OB.mg-1, 0,85x106 OB.mg- 1 and 2,55x106 OB.mg-1, demonstrating the importance of the kinetic parameters when comparing productivity between the systems and ensuring a better yield of the viral bioinsecticide. For expression vector construction, the total RNA obtained from brain tissue from mice infected with inactivated R. lyssavirus was used for cDNA construction and cloning into competent E. coli cells. Plasmid DNA was extracted, but there was a low amplification of the glycoprotein gene.